Transmission through subwavelength slit structures with a double period: A simple model for the prediction of resonances - Skigin, Diana Carina (2009)
Transmission wire gratings comprising several subwavelength slits within each period (compound gratings) have been shown to exhibit abrupt dips in the transmission response. These minima correspond to phase resonances, that are excited in the structure when a particular distribution of the magnetic field phases inside the slits is generated. By using an approximate model based on the modal method, we can easily obtain the resonant frequencies which correspond to transmittance maxima (Fabry-Perot resonances) and minima (phase resonances). This simplified model constitutes a practical tool to accurately predict the relevant characteristics of the transmitted response of compound structures for normal and oblique incidence, without a full solution of the scattering problem. © 2009 IOP Publishing Ltd.